Src homology 2 domain-containing leukocyte phosphoprotein of 76 kDa and phospholipase Cγ1 are required for NF-κB activation and lipid raft recruitment of protein kinase Cθ induced by T Cell costimulation - Dienz, Oliver; Krammer, Peter H. (The journal of immunology, 2003)
The NF-κB activation pathway induced by T cell costimulation uses various molecules including Vav1 and protein kinase C (PKC)θ. Because Vav1 inducibly associates with further proteins including phospholipase C (PLC)γ1 and Src homology 2 domain-containing leukocyte phosphoprotein of 76 kDa (SLP-76), we investigated their role for NF-κB activation in Jurkat leukemia T cell lines deficient for expression of these two proteins. Cells lacking SLP-76 or PLCγ1 failed to activate NF-κB in response to T cell costimulation. In contrast, replenishment of SLP-76 or PLCγ1 expression restored CD3/CD28-induced IκB kinase (IKK) activity as well as NF-κB DNA binding and transactivation. PKCθ activated NF-κB in SLP-76- and PLCγ1-deficient cells, showing that PKCθ is acting further downstream. In contrast, Vav1-induced NF-κB activation was normal in SLP-76− cells, but absent in PLCγ1− cells. CD3/CD28-stimulated recruitment of PKCθ and IKKγ to lipid rafts was lost in SLP-76- or PLCγ1-negative cells, while translocation of Vav1 remained unaffected. Accordingly, recruitment of PKCθ to the immunological synapse strictly relied on the presence of SLP-76 and PLCγ1, but synapse translocation of Vav1 identified in this study was independent from both proteins. These results show the importance of SLP-76 and PLCγ1 for NF-κB activation and raft translocation of PKCθ and IKKγ.
Gesehen am 08.04.2021